Minimally invasive surgery for placement of a subcutaneous EEG implant - Djurhuus, Bjarki D.; Viana, Pedro F.; Ahrens, Esben; Nielsen, Sofie S.; Srinivasan, Harishchandra L.; Richardson, Mark P.; Homøe, Preben; Hasegawa, Harutomo; Zarei, Ali A.; Gauger, Pia L. K.; Duun-Henriksen, Jonas (Frontiers in Surgery, 2023)
Background: A new class of subcutaneous electroencephalography has enabled ultra long-term monitoring of people with epilepsy. The objective of this paper is to describe surgeons' experiences in an early series of implantations as well as discomfort or complications experienced by the participants. Methods: We included 38 implantation procedures from two trials on people with epilepsy and healthy adults. Questionnaires to assess surgeons' and participants' experience were analyzed as well as all recorded adverse events occurring up to 21 days post-surgery. Results: With training, the implantation could be performed in approximately 15 minutes. Overall, the implantation procedure was considered easy to perform with only 2 episodes where the implant got fixated in the introducing needle and a new implant had to be used. The explantation procedure was considered effortless. In 2 cases the silicone sheath covering the lead was damaged during the explantation, but it was possible to remove the entire implant without leaving any foreign body under the skin. Especially in the trial on healthy participants, a proportion experienced adverse events in the form of headache or implant-pain up to 21 days post-operatively. In 6 cases, adverse events contributed to the decision to explant and discontinue the study: Four of these cases involved implant pain or headache; One case involved a post-operative local infection; and in one case superficial lead placement resulted in skin perforation a few weeks after implantation. Conclusion: The implantation and This is a provisional file, not the final typeset article explantation procedures are considered swift and easy to perform by both neurosurgeons and ENT surgeons. The implant is well tolerated by most participants. However, headache or pain around the implant can occur for up to 21 days post-operatively as anticipated with any such surgery. The expected benefits from the implant should always outweigh the potential disadvantages.